The Influence of Watching TikTok Content @buiramara on Knowledge and Motivation to Complete Final Projects Among Communication Science Students at UIN Sumatera Utara - manurung, afwan; Humaizi, Humaizi; Zulkarnain, Iskandar (Lafadz Jaya Publisher, 2024)
This study aims to analyze the effect of watching TikTok @buiramira content on the knowledge and motivation to complete final projects among Communication Science students at UIN North Sumatra. A quantitative approach with a correlational method was employed, utilizing viewing theory (viewing intensity), knowledge theory (knowledge level), and motivation theory (student motivation after consuming TikTok @buiramira content). The population consists of Communication Science students in semesters 6-8, with purposive and accidental sampling techniques used to select the sample. A questionnaire was distributed to 100 respondents. Data analysis involved single table analysis, cross-tabulation, correlation tests, and hypothesis testing. Results indicate a significant influence of watching TikTok @buiramira content on knowledge, with a Sig value of 0.000 < 0.005, and a moderate influence with a correlation value of 0.570. Similarly, there is a significant influence on motivation, with a Sig value of 0.000 < 0.005, and a moderate influence with a value of 0.601. Combined, the influence on both knowledge and motivation is significant, with a Sig value of 0.000 < 0.005 and a moderate influence with a value of 0.716, indicating a positive relationship approaching 1.